THE IMPORTANCE OF INTENSIVE TREATMENT IN THE REHABILITATION PROCESS OF CHILDREN WITH AUTISM SPECTRUM DISORDER (Annual of the Faculty of Philosophy in Skopje, 2019)
Autism is a pervasive developmental disorder defined by the presence of abnormaland impaired development manifested before the third year of life with a specifictype of pathological functioning in all three areas of social interactions, communicationand by repetitive behaviour (WHO, 2018).The starting point of this study is whether and to what extent the intensivetreatment affects the condition of each child with an autism spectrum disorder. Theresults from the research demonstrate the existence of a significant improvement ofthe condition of children with autism spectrum disorder in intensive treatment duringthe assessment after a certain period of time.